Economic Downturn, Economic Recovery, Economic Indicators, and Investment Opportunities - Singco, Jeshua Mel C.; Narsico, Peter G.; Narsico, Lalaine O.; Polinar, Mark Anthony N. (Future Science / FSH-PH Publications, 2024)
Economic downturns represent an inevitable challenge that nations and businesses must confront, presenting considerable risks. As a result, it becomes imperative for them to formulate strategies to secure their survival. The world has recently experienced an economic downturn due to a pandemic. COVID-19 has caused a significant economic crisis, leading to job losses and disruptions across various sectors worldwide, including the Philippines. The study utilizes economic indicators to determine patterns, meanings, and subsequent opportunities. Specifically, the study sought to identify relevant economic indicators, find patterns and meaning within each indicator and among indicators, and determine implications from findings. Content analysis was used in the study. It is a qualitative research method to identify and interpret themes, meanings, and patterns. The materials used include eleven Philippine economic indicators, namely, the Philippine Stock Exchange Composite Index, Balance of Trade, Core Inflation Rate, Consumer Spending, Tourist Arrivals, Consumer Confidence, Consumer Credit, Gold Reserves, Foreign Exchange Reserves, and Money Supply M2, and Interest Rate. In conclusion, the study determined that the collective surge in economic activities is positively related to the rise of inflation; increased interest rates potentially mitigated the rise in inflation, and other factors negated the trade deficits and gold reserve fluctuations. The Philippine economy is on the path to recovery, and the unique interrelations of economic indicators imply a more stable environment in the Philippine economy. This signals a green light for investors and an opportunity for policymakers to fine-tune existing initiatives to sustain economic recovery.